Optic disc edema and chorioretinal folds develop during strict 6° head‐down tilt bed rest with or without artificial gravity. Issue 15 (6th August 2021) - Laurie, Steven S.; Greenwald, Scott H.; Marshall‐Goebel, Karina; Pardon, Laura P.; Gupta, Akash; Lee, Stuart M. C.; Stern, Claudia; Sangi‐Haghpeykar, Haleh; Macias, Brandon R.; Bershad, Eric M.
Abstract: Spaceflight associated neuro‐ocular syndrome (SANS) is hypothesized to develop as a consequence of the chronic headward fluid shift that occurs in sustained weightlessness. We exposed healthy subjects ( n = 24) to strict 6° head‐down tilt bed rest (HDTBR), an analog of weightlessness that generates a sustained headward fluid shift, and we monitored for ocular changes similar to findings that develop in SANS. Two‐thirds of the subjects received a daily 30‐min exposure to artificial gravity (AG, 1 g at center of mass, 0.3 g at eye level) during HDTBR by either continuous (cAG, n = 8) or intermittent (iAG, n = 8) short‐arm centrifugation to investigate whether this intervention would attenuate headward fluid shift‐induced ocular changes. Optical coherence tomography images were acquired to quantify changes in peripapillary total retinal thickness (TRT), retinal nerve fiber layer thickness, and choroidal thickness, and to detect chorioretinal folds. Intraocular pressure (IOP), optical biometry, and standard automated perimetry data were collected. TRT increased by 35.9 µm (95% CI, 19.9–51.9 µm, p < 0.0001), 36.5 µm (95% CI, 4.7–68.2 µm, p = 0.01), and 27.6 µm (95% CI, 8.8–46.3 µm, p = 0.0005) at HDTBR day 58 in the control, cAG, and iAG groups, respectively. Chorioretinal folds developed in six subjects across the groups, despite small increases in IOP. Visual function outcomes did not change. These findings validate strict HDTBR without elevated ambient CO2 as a model for investigating SANS and suggest that a fluid shift reversal of longer duration and/or greater magnitude at the eye may be required to prevent or mitigate SANS. Abstract : Spaceflight associated neuro‐ocular syndrome (SANS) is hypothesized to develop as a consequence of the chronic headward fluid shift that occurs in sustained weightlessness. To investigate this condition, healthy subjects were exposed to strict 6º head‐down tilt bed rest (HDTBR), a spaceflight analog that causes a chronic headward fluid shift and can lead to the development of optic disc edema in some participants. For the first time, we demonstrate that chorioretinal folds develop during HDTBR, along with signs of optic disc edema, similar to findings that occur in astronauts during spaceflight. However, ocular changes were not mitigated in subjects who were exposed for 30 min per day to continuous or intermittent artificial gravity (AG) via centrifugation during HDTBR. These findings validate strict HDTBR without elevated ambient CO2 as a model for investigating these ocular changes and suggest that a fluid shift reversal of longer duration and/or greater magnitude at the eye than used here may be required to prevent or mitigate spaceflight associated neuro‐ocular syndrome findings.